All Life Is a Circle: Poetry and the Search for My Native American Roots. (1st October 2016) - Lang Day, Lucille
Abstract : In this personal essay, which includes five poems, the author uses poetry as a vehicle to recover, connect with, and explore her Native American ancestry. Her mother, who was one-quarter Wampanoag, was raised from age seven by a couple who taught her that Native American ancestry was something to hide. The poems are interwoven with the account of the author's struggle to retrieve a family story that has been intentionally suppressed. In the first poem, the author's connection to her Native American roots is reflected purely through her interest in and reverence for the earth and its creatures, but throughout the article, the connection becomes a progressively more specific bond with a particular ancestor and his tribe. As the author draws closer to identifying her Wampanoag great-grandfather through genealogical research and reaching out to Wampanoag tribes in Massachusetts, she also draws closer to his spirit, and she writes the final poem, "Wampanoag Clambake, " in his voice.